Категория презенса и его языковая реализация в текстах разностилевой направленности - Бадрутдинова, В.А.; Исаев, Э.Ш. (Культура народов Причерноморья, 2014)
Предметом рассмотрения данного исследования является временная форма презенс, его
многозначность и способность выражать действие в будущем времени. В ходе исследования удалось
выявить условия, при которых презенс выражает действие в будущем времени. Предметом розгляду даного дослідження є часова форма презенс, його багатозначність і
здатність виражати дію в майбутньому часі. У ході дослідження вдалося виявити умови, за яких
презенс виражає дію в майбутньому часі. The focus of this study is the category of the Present tense, its ambiguity and its ability to express the
Future time action. The research finding is the conditions under which the category of the Present tense
expresses the Future time action. The Present tense has the greatest ambiguity. Almost all well-known authors of
grammar books emphasize that the Present tense may be relevant both to the present, future, and past time. In
the German language the forms of Future and of the Present tense with the future meaning compete between
themselves to express the future time. According to the analysis of a large number of texts belonging to different
styles, the Present tense with the future meaning is more often used with time expressions (dates, adverbs of time,
etc.) (35.5%) than the Future tense (24 %), which generally indicates a greater dependence of this tense form on
the context presupposing a future time. However, time expressions’ semantics plays a key role in the usage of
these forms. So, it should be noted that sentences which have exact indication of time are usually used in
dialogues of characters of literary works and the form of the Future tense that is observed in them is exclusively
the Present tense with the future meaning. In sentences with explicit, more or less distinct localization of actions
in the future, mainly the Present tense with the future meaning is used. And in sentences with reference to the
"indefinite future", especially with such expressions as eines Tages (eines Morgens), mal, einmal, irgendwann,
in Zukunft, mainly the Future tense is used. In this regard, we can speak about the predisposition of the Present
tense with the future meaning to the “definite” future, and of the Future tense - to the designation of "indefinite”
future. There are some commonly known adverbs of time which transform the action of the Present tense to the
action of the Future tense. With adverbs and phrases of futurity the future meaning of the Present tense is given
only as a special, particular meaning. Consider some adverbs that transform the action of the Present tense to
the action of the Future tense. E.I. Shendels gives quite a limited number of adverbs with the meaning of futurity:
bald, morgen, in kurzer Zeit, in einigen Stunden, in einer Woche, am nächsten Tag ua.